Carry funding and safe haven currencies: A threshold regression approach - Oliver Hossfeld; Ronald MacDonald (Deutsche Bundesbank, 2014)
In this paper, we analyze which currencies can be regarded as safe haven currencies. Our empirical approach allows us to distinguish between a low- and high stress regime, and to control for the impact of carry trade reversals and other fundamental determinants. We therefore address the question of whether a supposed safe haven currency only appreciates in times of crises because carry trades are unwound, in which the corresponding currency has served as funding currency, or whether it possesses 'true' safe haven qualities; i.e. it provides a hedge against global stock market losses in stressful times even after controlling for the impact of carry trade reversals. The latter issue has largely been brushed aside in the extant literature but has important policy implications for the justification of central bank FX interventions in times of crises. According to the estimation results, two currencies, the Swiss franc and (to a lesser extent) the US dollar qualify as safe haven currencies, and the euro serves as a hedge currency. Results for the yen support its role as a carry funding vehicle, but not necessarily that of a safe haven currency. While the focus is on effective exchange rates, the paper also contains a separate analysis of bilateral euro-based exchange rates, given the euro's prominent role during the euro area sovereign debt crisis.
Keywords: C32; F31; 330; Nonlinear Regression; Threshold Model; Safe Haven; Carry Trade